On the modelling of precipitation kinetics in a turbine disc nickel based superalloy. (1st June 2020) - Anderson, M.J.; Schulz, F.; Lu, Y.; Kitaguchi, H.S.; Bowen, P.; Argyrakis, C.; Basoalto, H.C.
Graphical abstract: Abstract: The precipitation kinetics of gamma prime in the nickel based superalloy RR1000 has been characterised after solid-solution heat treatments and isothermal aging conditions relevant to service conditions. Multi-modal precipitate dispersions are formed within the alloy. Numerical methods are presented for determining the three dimensional size of the particle populations combining information obtained from Scanning Electron microscopy and Transmission Electron microscopy. This information has been used to develop a multi-component mean-field model descriptive of precipitation kinetics. The smallest particle population increases in mean size during isothermal aging at 700 ∘ C where classical mean-field models of coarsening kinetics suggest that these particles should dissolve. A phenomenological model has been proposed to capture this behaviour within a statistical formulation that is applicable to both processing and service conditions.